A method to localize plasma density enhancements along lines of sight to radio sources through PSP/WISPR’s field of view - Kenny, Kenny N.; Kooi, Jason E.; Van Kooten, Samuel J.; DeForest, Craig E. (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionCoronal Faraday rotation (FR) measurements provide a powerful means of measuring the magnetic field of the solar corona and solar wind (along the line of sight (LOS) between a background linearly polarized radio transmitter and a ground-based radio receiver). FR is a path integrated quantity depending on both the plasma density (ne) and the magnetic field component along the LOS (B⃗LOS). Consequently, the fundamental calibration challenge encountered when using radio FR observations to infer the magnetic field structure of the solar wind is distinguishing between the ne and B⃗LOS contributions to the detectable FR.MethodsThe method presented here, however, will be able to provide localized plasma density information to FR observations for the first time. Using a synthetic field of view of the Wide-field Imager for Parker Solar Probe (WISPR), we perform a tomographic reconstruction of the plasma density in the vicinity of spacecraft.DiscussionThis article develops the framework to determine the positions, along LOS to radio sources, of the density enhancements we reconstruct tomographically.ConclusionWhile still in development, this method provides the necessary foundation to complement and enhance coronal FR measurements, but the applicability of this technique extends beyond coronal FR.